Effects of intuitive judgments on consumer assortment evaluations. Issue 3 (11th May 2015) - Piris, Yolande; Guibert, Nathalie
Abstract : Purpose: – This paper aims to apply intuition theory to clarify consumers' assortment evaluations. For each decision process, this paper explores how perceptions of organization and variety influence consumers' attitudes and purchase intentions. Design/methodology/approach: – In total, 504 observations were collected across three product categories. Perceived choice, time and expertise in the product category provide proxies to distinguish between intuitive and deliberative systems. The intuitive system further consists of intuition based on either expertise or heuristics. Findings: – It was revealed that distinct decision processes (deliberative, intuitive based on expertise and intuitive based on heuristics) affect the link between assortment perceptions and consumers' assortment evaluations. Consumers' evaluations in deliberative- and heuristic-based intuitive systems rely more on perceptions of organization than of variety; whereas intuitive judgments based on expertise depend almost equally on both perceptions. Research limitations/implications: – Some limitations have to be underlined. The approximations used could be more precise and are subjective in nature. Moreover, the ordinary product categories that were studied might encourage more intuitive decisions by consumers. If so, the deliberative mode of thinking might have been underrepresented in this sample. Originality/value: – Despite the limitations, this research is, to our knowledge, the first to explore the influence of intuition theory on ordinary shopping and in particular on assortment perception. As such, it contributes to a deeper understanding of this theory in the field.